2010
DOI: 10.1155/2010/103742
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Depression in Young Prader Willi Syndrome Patients following Clonidine Provocation for Growth Hormone Secretion Testing

Abstract: Objectives. To determine the sedative and respiratory effects of clonidine when used to evaluate growth hormone (GH) secretion in children with Prader Willi Syndrome (PWS). Methods. The study prospectively evaluated children with PWS who received clonidine (0.15 mg/m2) to assess GH responsiveness. Patients were studied up to four times over three years. Vital signs, oxygen saturation, and sedation level were recorded at baseline and every five minutes following clonidine. Changes between baseline and post-clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Various stimulation tests for GH secretion have been proposed over the years, each with its own advantages and limitations. 31 Hollmann et al 32 have recently shown that clonidine administration caused respiratory depression in some children with Prader-Willi syndrome. Of note is the fact that the usefulness of the clonidine test is limited to the paediatric age, because in adult subjects, the GH response to the drug was not different from that after placebo.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various stimulation tests for GH secretion have been proposed over the years, each with its own advantages and limitations. 31 Hollmann et al 32 have recently shown that clonidine administration caused respiratory depression in some children with Prader-Willi syndrome. Of note is the fact that the usefulness of the clonidine test is limited to the paediatric age, because in adult subjects, the GH response to the drug was not different from that after placebo.…”
Section: Discussionmentioning
confidence: 99%
“…2 Clonidine is an alpha-receptor agonist that stimulates GH secretion by a central mechanism probably by inducing endogenous GHRH release 26,27 and, among the various GH provocative tests, is one of the most widely used 28,29 in children. 32 However, respiratory dysfunction is a common finding in patients with Prader-Willi syndrome, contributing significantly to morbidity and early mortality in this population. 30 In our centre, the clonidine test is routinely used to evaluate GH secretion in children with short stature and/or poor growth velocity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations